2020
DOI: 10.1007/s00394-020-02200-9
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic supplementation with prebiotic green banana resistant starch and probiotic Bacillus coagulans spores ameliorates gut inflammation in mouse model of inflammatory bowel diseases

Abstract: Purpose The research goal is to develop dietary strategies to help address the growing incidence of inflammatory bowel diseases (IBD). This study has investigated the effectiveness of green banana resistant starch (GBRS) and probiotic Bacillus coagulans MTCC5856 spores for the amelioration of dextran-sulfate sodium (DSS)-induced colitis in mice. Methods Eight-week-old C57BL/6 mice were fed standard rodent chow diet supplemented with either B. coagulans, GBRS or its synbiotic combination. After 7 days supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
57
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 80 publications
(111 reference statements)
11
57
2
Order By: Relevance
“…These molecules then interact with other immune cells through a complex network of signaling pathways, leading to the activation of the mucosal immune systems. Specific PBs have been demonstrated to enhance T-helper 1 (Th1) and regulatory T-cell (Treg) function [75] and strengthen the epithelial barrier function by increasing mucin production, tight junction proteins, and goblet cells [76][77][78]. In contrast to some earlier reports [79][80][81], current studies support the potency of specific PBs in inducing changes in gut bacterial diversity [82][83][84].…”
Section: Probioticscontrasting
confidence: 41%
See 2 more Smart Citations
“…These molecules then interact with other immune cells through a complex network of signaling pathways, leading to the activation of the mucosal immune systems. Specific PBs have been demonstrated to enhance T-helper 1 (Th1) and regulatory T-cell (Treg) function [75] and strengthen the epithelial barrier function by increasing mucin production, tight junction proteins, and goblet cells [76][77][78]. In contrast to some earlier reports [79][80][81], current studies support the potency of specific PBs in inducing changes in gut bacterial diversity [82][83][84].…”
Section: Probioticscontrasting
confidence: 41%
“…The variations in the formulation of prebiotic supplements in these studies could account for the discrepancies in the status of participants and outcomes. The type of prebiotic fiber, its complexity (purified or whole-plant) and added bio-actives tend to considerably influence the benefits achieved [77,78].…”
Section: Prebiotic Dfmentioning
confidence: 99%
See 1 more Smart Citation
“…S. boulardii ma c-1701 inclusion showed some alterations with regard to microbiota communities. In the colon, S. boulardii ma c-1701 inclusion increased the abundance of Bacillus genus, which have excellent immunomodulatory and anti-in ammatory e cacy [40,41]. In addition, a previous study reported that several Bacillus species, reduced pathogen colonization but the mechanisms by which this occurs is unclear [42].…”
Section: Discussionmentioning
confidence: 99%
“…boulardii ma c-1701 inclusion showed some alterations with regard to microbiota communities. In the colon, S. boulardii ma c-1701 inclusion increased the abundance of Bacillus genus, which have excellent immunomodulatory and anti-in ammatory e cacy [38,39]. In addition, a previous study reported that several Bacillus species, reduced pathogen colonization but the mechanisms by which this occurs is unclear [40].…”
Section: Discussionmentioning
confidence: 99%